The violent bear it away - O'Connor, Flannery (New York : Farrar, Straus and Giroux, 1988)
Francis, an orphan who lives with his great-uncle in Powderhead, Tennessee, is called by God to be a prophet. This is against his will and causes much inner conflict.
Wilson's Fiction.
Adult
Keywords: Great-uncles -- Tennessee -- Fiction; Orphans -- Tennessee -- Fiction; Prophets -- Tennessee -- Fiction; Great-uncles -- Fiction; Orphans -- Fiction; Prophets -- Fiction; Tennessee -- Fiction